2005
DOI: 10.1186/1471-2202-6-43
|View full text |Cite
|
Sign up to set email alerts
|

Amplitude-dependency of response of SI cortex to flutter stimulation

Abstract: Background: It is established that increasing the amplitude of a flutter stimulus increases its perceived intensity. Although many studies have examined this phenomenon with regard to the responding afferent population, the way in which the intensity of a stimulus is coded in primary somatosensory cortex (SI) remains unclear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(19 citation statements)
references
References 29 publications
0
19
0
Order By: Relevance
“…Further, the evidence presented here strongly suggests that the improved discriminability with adaptation results from a sharpening of the spatial response at the level of S1. Intrinsic optical imaging results in the anesthetized monkey have pointed to such a sharpening effect with adaptation (Simons et al, 2005; Tommerdahl et al, 2002). In previous studies in the vibrissa pathway, some evidence for spatial sharpening has been demonstrated in single unit recordings (Brumberg et al, 1996), local field potentials and intrinsic optical imaging (Sheth et al, 1998), and VSD imaging (Kleinfeld and Delaney, 1996), leading to speculation that this could enhance discriminability (Moore, 2004; Moore et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Further, the evidence presented here strongly suggests that the improved discriminability with adaptation results from a sharpening of the spatial response at the level of S1. Intrinsic optical imaging results in the anesthetized monkey have pointed to such a sharpening effect with adaptation (Simons et al, 2005; Tommerdahl et al, 2002). In previous studies in the vibrissa pathway, some evidence for spatial sharpening has been demonstrated in single unit recordings (Brumberg et al, 1996), local field potentials and intrinsic optical imaging (Sheth et al, 1998), and VSD imaging (Kleinfeld and Delaney, 1996), leading to speculation that this could enhance discriminability (Moore, 2004; Moore et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…A wide range of studies characterizing cortical representations in the face of persistent or adapting stimuli (Lee and Whitsel, 1992; Sheth et al, 1998; Simons et al, 2005) have made qualitative inferences regarding the relationship between the observed spatial sharpening and the improved acuity in psychophysical studies (Tannan et al, 2006; Vierck and Jones, 1970). It is important to note, however, that a sharpened cortical response alone is not sufficient to improve discriminability, and that in many cases sharpened representations can lead to a reduction in information transmission (Pouget et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This supports the view that spikecount-based neural codes may be more suitable for representing the stimulus magnitude as presented in the current paper. Furthermore, optical intrinsic imaging revealed that as the stimulus amplitude is increased, the spatial spread of cortical activation remains relatively constant while the activity within this region progressively increases (Simons et al 2005). The activity in the immediate surrounding regions decreases due to inhibition and this may be the evidence for contactor size decoding performed by the somatosensory cortex to disentangle stimulus intensity and contactor size.…”
Section: ; Dementioning
confidence: 97%
“…Using these techniques, consistent abnormalities in basic tactile detection and thresholds, and difficulties with tactile adaptation (i.e., the ability to adjust one’s sense based upon prior sensory experiences) have been identified for individuals with ASD (Puts et al 2014). While for typically developing (TD) individuals the presence of an adapting stimulus is thought to reduce the perceived intensity of subsequent stimuli through alterations in neuronal firing (Simons et al 2005); this effect is not consistently observed in individuals with ASD. Specifically, amplitude discrimination (i.e., the ability to identify which stimulus is stronger) and detection threshold (i.e., the minimum stimulus that can be perceived) in TD adults and children worsens with presentation of an adapting stimulus; this effect is not observed in adults and children with ASD (Tommerdahl et al 2007; Puts et al 2014).…”
Section: Introductionmentioning
confidence: 99%